ADHESI KERATINOSIT KULIT MANUSIA PADA PLASTIK CLING WRAP BERLEM FIBRIN DAN BERLEM GEL PLATELET-RICH PLASMA (PRP) - , dr. Sa,adatul Huriyah, dr. Yohanes Widodo Wirohadidjojo, SpKK(K) ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Cling wrap has properties similar to Tegadermâ¢, an expensive band-aid that has been used as a transport membrane of keratinocytes. PRP gel and fibrin glues are proved to be useful as the cellular adhesive on cellular transplantation. We hypothesized that either PRP gel or fibrin glues can enhance plastic-keratinocytes adhesion and can be used as a replacement material for Tegadermâ¢. In order to have an evidence of our hypothesis, an invitro study was designed to determine passage 2 human keratinocytes adhesion on cling wrap and compared to Tegadermâ¢. Forty micro liters of 1 x 105 keratinocytes/mL were dropped onto cling wraps and Tegadermâ¢ either coated by fibrin glues or PRP gel. Measurement of keratinocytes adhesion was using the MTT-assay, performed after 72 hours incubation, and read by 570 nm of spectrometer. Improving of research validity was performed by eight times repeated procedures. The means of optical density of blue formazan among various groups were analyzed using the one-way Anova and Kruskal Wallis test with post hoc analysis by Mann-Whitney test. The results showed adhesion of keratinocytes on uncoated cling wrap better than uncoated Tegadermâ¢ (P<0,05). Fibrin glue coating on the cling wrap significantly (P<0.05) enhanced the adhesion of keratinocytes. This adhesion is equal to fibrin glue coated Tegaderm â¢. This fact is not found among PRP gel coated cling wrap. Conclusion, cling wrap can be used as keratinocyte transport membrane in cellular grafting